Poezja bez granic. Ania Walwicz - Andrzej Jaroszyński (Postscriptum Polonistyczne)
This is a presentation of the prose poetry of Ania Walwicz, one of Australia’s bestknown experimental writers and performers but unknown in Poland. Her two pieces: Australia and Poland are given special attention to show some of the fundamental features of her poems, i.e. loss of identity and transgressive forms of her language. A short recollection of the author’s encounter with the poet in 2012 is included as well.